Pendampingan Holistik untuk Wanita dengan Sindrom Perimenopause di Desa Mantang, Kecamatan Batukliang - Puspita, Sylvia; Ningsih, Nining Fatria; Wahyuni, Ervin Dini (CV Putra Publisher, 2025)
Menopause is a natural phase experienced by every woman, marked by the cessation of menstruation and significant hormonal changes. The perimenopausal process can affect both physical and psychological conditions, often causing symptoms such as hot flashes, sleep disturbances, and feelings of anxiety. In Mantang Village, Batukliang District, this community service program aims to provide holistic support for women aged 40-55 who are experiencing perimenopause. A participatory approach is used to actively involve the community in education about physical and psychological changes, as well as symptom management. Activities include group education, individual counseling, and workshops on symptom management using relaxation techniques and healthy eating habits. A total of 26 participants took part in this program, and evaluations through pretests, posttests, and in-depth interviews showed a significant improvement in participants' understanding of perimenopause and their ability to manage symptoms. The educational calendar provided was also proven effective as a daily reminder tool. These results indicate that structured interventions can improve the quality of life for perimenopausal women and provide essential emotional support in navigating this transition.